A 2000-year leaf wax-based hydrogen isotope record from Southeast Asia suggests low frequency ENSO-like teleconnections on a centennial timescale. (15th September 2016) - Yamoah, Kweku A.; Chabangborn, Akkaneewut; Chawchai, Sakonvan; Schenk, Frederik; Wohlfarth, Barbara; Smittenberg, Rienk H.
Abstract: Limited understanding of the complex dynamics of the tropical monsoon exists, partly due to inadequate paleo (hydro)-climate proxy data from monsoonal regions. This study presents a 2000-year long record of hydrogen isotope values of leaf wax (δDwax ) from a sedimentary sequence recovered from Lake Pa Kho, Northern Thailand. Evaluation of present day rainfall patterns and water isotope data indicates that δDwax reflects the amount of rainfall and is also influenced by El Niño-Southern Oscillation (ENSO) dynamics. Over the last 2000 years, wettest conditions occurred between ca . 700 AD and ca . 1000 AD, whereas the driest intervals lasted from ca . 50 BCE to ca . 700 AD and from ca . 1300 AD to ca . 1500 AD. Further investigations to establish the spatiotemporal variability of ENSO within the wider tropical Asian-Pacific realm over centennial timescales revealed a low-frequency-tripole pattern between mainland SE Asia (MSEA), the tropical West Pacific, and the central-eastern Pacific, with a wetter than normal MSEA during El Niño-like climate conditions. This pattern stands in contrast to the annual event where El Niño cause drier conditions in MSEA. We hypothesize that on centennial timescales the land-sea contrast, which drives monsoon intensity in MSEA, is modulated by the latitudinal shift of the Walker circulation and associated ENSO dynamics. Highlights: δD of precipitation in Thailand is dominated by the amount effect and ENSO dynamics on annual timescales. Mainland SE Asia becomes wetter and drier during El Niño and La Niña-like climate, respectively, on centennial timescales. Our study provides empirical support for observed composite ENSO pattern extracted from instrumental data.